Gesture based wireless control for a robotic manipulator - Vijay Joseph, Arockia; Mathur, Akshat; Verma, Jatin; Singh, Ankita (International Journal of Engineering and Technology, 2018)
This project plays a very important role to complement the industrial and automation field. Nowadays, robots are used in several fields of engineering and manufacturing and the systems for controlling or actuating them have also enhanced from the past. The use of gestures for controlling them has been the new trend to control the movement of robotic manipulators. The various methodologies for controlling them are motion tracking, image processing and by using Kinect sensors. All these methods can be used as a teach pendant where one can provide the movement of the manipulator as a preset and the manipulator can carry out the same motion repetitively, or in the case of motion tracking and while using Kinect sensors, the user is bound to a confined area where the cameras can monitor the userâ€™s body. Here, we propose a wireless controlled robotic arm system for tool handling (pick and place) and many other applications where human reach is elusive. The result is that the gestures of the human hand are in sync with the manipulatorâ€™s movement. Further, this robotic arm has been implanted beneath a drone which would then have the ability to reach certain heights where human reach is impervious or might put a humanâ€™s life in jeopardy. In this case, the user can maneuver along with manipulator wherever it is used.Â Â